Reforming democracies : six facts about politics that demand a new agenda - Chalmers, Douglas A. (University seminars/Leonard Hastings Schoff memorial lectures., 2013)
Expanding our common understanding of the institutions of representative democracy, Douglas A. Chalmers examines six crucial aspects of political practice that are not included in the usual understanding of democratic institutions. They concern who the people are, how law and policy is made, and how the people are linked to that process. Chalmers argues that if we want to reform democracies, even ones considered established, we need to reform the democratic ordering of decision-making networks outside the legislatures and executives, to reconsider the role of information in law and policy deliberation, and to incorporate stake-holding noncitizens and foreigners into the political system.